(untitled) - JOVIC, FRAN (USA, 1992)
1.Signals, siystems and process control / 2.The basic process unit / 3.Stratification of control tasks and data communication / 4.The relative roles of software and hardware / 5.System software / 6.Application programs and databases / 7.Reduction and visualization of data and procedures / 8.Process management and control / 9.The role of the operator in process control y systems / 10.The feasibility study / 11.Computer control system desing / 12.Cost-effective system selection / 13.The integrated approach
Incluye bibliografia pag.415
Keywords: COMPUTADORES